Single‐cell dissection reveals immunosuppressive F13A1+ macrophage as a hallmark for multiple primary lung cancers - Chenglin Yang; Jiahao Qu; Jingting Wu; Songhua Cai; Wenyi Liu; Youjun Deng; Yiran Meng; Liuqing Zheng; Lishen Zhang; Li Wang; Xiaotong Guo (Clinical and Translational Medicine)
Abstract Background The increasing prevalence of multiple primarylung cancers (MPLCs) presents challenges to current diagnostic and clinicalmanagement approaches. However, the molecular mechanisms driving MPLCdevelopment and distinguishing it from solitary primary lung cancers (SPLCs)remain largely unexplored. Methods We performed a comparative single‐cell RNAsequencing (scRNA‐seq) analysis on tumour and adjacent para‐tumour tissues fromMPLC and SPLC patients to comparatively evaluate their immunological landscapes.Additionally, multiplex immunofluorescence (mIF) staining and independentvalidation datasets were used to confirm findings. Results MPLCs and SPLCs share significant similarities in genetic, transcriptomic and immune profiles, suggesting common therapeutic strategies such as EGFR‐TKIs andICIs. Notably, an immunosuppressive macrophage subtype, F13A1+ Macrophage (Mϕ), is specifically enriched in MPLCs. This subtype overexpresses M2 macrophagemarkers and exhibits up‐regulation of SPP1‐CD44/CCL13‐ACKR1 interactions, indicatingits role in shaping the immunosuppressive tumour microenvironment and promotingtumour growth in MPLCs. Conclusions This study unveils shared molecular mechanismsbetween MPLCs and SPLCs, while identifying MPLC‐specific cellular and molecularfeatures, such as the role of F13A1+ macrophages. The findings provide novelinsights into MPLC pathogenesis, supporting the development of targetedtherapeutic strategies. Key points Comparative scRNA‐seq analysis reveals significant similarities in genetic, transcriptomicand immune profiles between MPLCs and SPLCs. Identification of a unique immunosuppressive F13A1+ macrophage subtype, preferentially enriched in MPLCs, linked to immune evasion and tumourprogression. SPP1‐CD44/CCL13‐ACKR1 interactions are crucial in MPLC tumour microenvironment, indicating potential targets for therapeutic intervention.